3298 Diabetes Prevalence in Rural and Urban Patients Seeking Care from the Veterans Health Administration (VHA): 2007-2012. (27th March 2019) - Medunjanin, Danira; Davis, Melanie L.; Wojciechowski, Barbara; Lynch, Cheryl P.; Dismuke, Clara E.; Neelon, Brian; Axon, Neal; Hunt, Kelly J.
Abstract : OBJECTIVES/SPECIFIC AIMS: To examine rural-urban disparities in prevalence of diagnosed diabetes in veterans receiving care at the VA and to determine the extent to which demographic factors and obesity levels contribute to identified disparities. METHODS/STUDY POPULATION: A retrospective serial cross-sectional analysis was employed. A stratified weighted random sample of veterans who received care at a VA facility was selected each year for 2007 through 2012. Rural Urban Commuting Area (RUCA) codes were based on resident zip code. Diabetes was defined by two or more primary or secondary ICD-9 codes for diabetes (250.xx) within a 12 month period. Data were analyzed using complex survey-specific procedures. RESULTS/ANTICIPATED RESULTS: Diabetes prevalence 2007-2012 was lowest in urban (20.5%-21.0%), followed by highly rural (21.1%-22.1%) and rural (22.3%-23.0%) areas with the prevalence being significantly higher on the insular islands (31.0%-32.4%). In 2012, 41% of urban, 43% of rural and highly rural and 30% of insular island veterans were obese. Relative to urban areas, the odds ratio for prevalent diabetes was 1.10 (95% CI: 1.08, 1.12) for rural veterans, 1.19 (95% CI: 1.16, 1.23) for insular island veterans, and 1.00 (95% CI: 0.98, 1.02) for highly rural veterans. DISCUSSION/SIGNIFICANCE OF IMPACT: Prevalence of diagnosed diabetes is high in veterans residing in rural, highly rural and urban areas, but markedly higher on the insular islands. Understanding the burden of disease and factors driving disparities provides information required to develop targeted interventions.